Stakeholder Management: State of the Art and Perspectives - Mascena, Keysa Manuela Cunha de; Stocker, Fabricio (Future Studies Research Journal: Trends and Strategies, 2020)
Purpose – this research aims to present an overview of the stakeholder management, reviewing the main models and theoretical propositions and investigating the phenomena addressed in the empirical papers on the theme. Design/methodology/approach – A bibliometric survey and sociometric analysis were undertaken considering the international and national publications related to the topic between 1980 and 2019. Originality / Value: The stakeholder approach has developed in recent years and its application is increasingly present in several areas of management, having a strong dialogue on the emerging issues of society. This study has an academic relevance advancing the dissemination of current knowledge in stakeholder theory integrating to the empirical studies. Findings – the main results were discussed in order to analyze: the variables related to stakeholder management; the stakeholder management models applied in empirical studies; the main results in studies on stakeholders’ conflict of interest; and discussions about stakeholder influence and pressure. Research implications – The research contribution consists in the elaboration of a panorama of the stakeholder management, presenting the main theoretical and empirical contributions, and the dimensions for future studies perspectives, being: i) Creation, co-creation and value distribution; ii) cooperation, involvement, and stakeholder engagement; iii) Influence of stakeholder management on performance; and iv) networks, relationships, and multi-stakeholder influences.